Engaging citizens in driverless mobility: Insights from a global dialogue for research, design and policy. (September 2021) - Chng, Samuel; Kong, Penny; Lim, Pei Yi; Cornet, Henriette; Cheah, Lynette
Highlights: We report findings from Driverless Mobility Citizen Dialogues held across 15 cities. Lay citizens were optimistic for driverless mobility despite technological and implementation concerns. Active leadership of governments was preferred to ensure safe and equitable driverless mobility. Accessible explanations of AV technology, standards and impacts on mobility and society need to be developed. The Citizen Dialogue provided richer insights than traditional methods (e.g., surveys and interviews). Abstract: Engaging lay citizens and eliciting their inputs, concerns and aspirations are important for industry and policymakers when developing and implementing driverless mobility. We present findings from a series of Citizen Dialogues on driverless mobility attended by 945 citizens in 15 cities across North America, Europe and Asia. The dialogue used a combination of qualitative and quantitative methods and was deliberative in nature to instil realism and provide richer insights. In all cities we found optimism for driverless mobility. Nevertheless, citizens exhibited lower levels of trust and acceptance as vehicle automation increased and this is potentially related to how automation levels are currently presented; in an incremental fashion leading to the perception that vehicle automation gets increasingly difficult, complex, and thus potentially dangerous. We identified a need for further investigation into how trust and acceptance are related with perceptions and understandings of automation levels, and how vehicle automation should be communicated to citizens more effectively. Findings further showed that public transport was the preferred implementation model for driverless mobility. National governments were most trusted to lead the development and implementation of driverless mobility in all cities as they are trusted to safeguard the interest of citizens with integrity and hold the authority for developing and setting standards and regulating autonomous vehicle technology. Building on our findings, we discuss implications and propose recommendations for industry, policymakers and researchers.